ANALISIS FAKTOR PENYEBAB KECELAKAAN LALU LINTAS JALAN PANTURA (RUAS JALAN KM 10 – KM 20) KABUPATEN TUBAN - Al Hakim, Subhan Akbar; Eddi Indro Asmoro; Asteria Narulita Pramana (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
A study conducted in Tuban Regency reveals that the area is prone to accidents and requires a thorough inspection. To determine which roads are accident-prone, the study used data on the volume of vehicle traffic and frequency of traffic accidents in 2023. The Accident Equivalent Number (AEK) method was used to calculate the accident rate, while the Z-score method was used to identify accident-prone points. Additionally, Collision diagrams were used to determine the factors contributing to accidents. The study found that in 2023, there were 0.62 casualties per million vehicle kilometers in the categories of death, serious injury, and minor injury. Furthermore, there were 0.09 casualties per million vehicle kilometers for severe injuries, 0.09 casualties per million vehicle kilometers for minor injuries, and 3.93 fatalities per million vehicle kilometers. The analysis identified human factors such as driving too fast, fatigue, and sleepiness, as well as road conditions including damaged or missing signs, road deterioration, and lack of infrastructure and facilities, such as street lights and traffic signs, as the main causes of accidents.